Research on hydrothermal petroleum and its organic matter - Jiyuan You; Yiqun Liu; Yijun Li; Dingwu Zhou; Zhexuan Li; Yiyao Yang (地质科技通报, 2021)
The causes of oil and natural gas formation have long been controversial about organic and inorganic causes. In recent years, the discovery of hydrothermal genesis in different oceans around the world has further provided new thinking for the exploration of oil and gas genesis. On the basis of reviewing the basic theory of organic oil-producing hypothesis, inorganic oil-producing hypothesis and the dispute between the two, authors focused on the characteristics and research progress of hydrothermally derived petroleum and its organic matter. Then combined with the study of hydrothermal jet deposition in the source rocks of Santanghu Basin and Ordos Basin, the following important insights were obtained: ①The organic matter derived from hydrothermal oil is derived from terrestrial higher plants and lower ocean organisms, the latter being thermophilic, poisonous, and high temperature resistant organisms living around hydrothermal vents. ②Hydrothermal oil does not need to be buried to continuously provide heat, and submarine hydrothermal activities provide material and heat for it. ③In the process of physicochemical interaction between organic matter and deep-source thermal material fluid, organic matter is "instantaneously" (short time) pyrolyzed into oil and partially converted into petroleum-like products. The study of hydrothermally oil and its organic matter can not only deepen people's understanding of the causes of oil and gas, but also have great significance for the exploration and development of unconventional oil.